Dampak Peredaran Obat Ilegal Lintas Negara terhadap Kesehatan Masyarakat Global dan Strategi Penanggulangannya - Meilinasary, Khairunnisa Azani; Malindea, Chinda; Athirah; Andriani, Yeni; Shofiaa, Lulu Dhiya (Program Studi Farmasi Sekolah Tinggi Ilmu Kesehatan Sambas, 2025)
The World Health Organization (WHO) established an international organisation known as the Member State Mechanism, aimed at combating the circulation of falsified and substandard medicines to ensure that the global population has access to high-quality, safe, and affordable medicines. Indonesia, as one of the member countries, has consistently taken an active role in this forum. However, in reality, both Indonesia and other countries around the world have not yet succeeded in overcoming this issue. The widespread circulation of falsified and substandard medicines poses significant risks to global public health. The objective of this study is to examine the impact of falsified and substandard medicines on global public health and to analyze the efforts undertaken by Indonesia and other countries to handle the proliferation of these medicines. This article employs a qualitative research method with an explanatory approach. The concepts of international cooperation and international regimes are used to explain the outcomes of collaboration within the Member State Mechanism and the role of WHO as an international organization in supporting efforts to combat counterfeit medicines. The result of this study is to illustrate the negative impacts caused by the circulation of falsified and substandard medicines, as well as the challenges faced by Indonesia and other countries in addressing the issue. These challenges stem from two main sources: external factors related to international cooperation, and internal factors stemming from domestic conditions.